IbM Kelompok Pembudidaya Ikan DI Desa Tunas Muda Ddalam Mengefisiensikan Biaya Pakan - Sarmila Sarmila; Sri Warastuti; Suparmin Suparmin; Rizal Akbar Hutagalung (Kapuas, 2021)
The group of Longgang Dalam fish farmers and PKK groups as partner groups in Tunas Muda Village are cultivating fish as a side activity, so it has not been so focused on efforts to increase production targets. This is due to the limited knowledge, information and mastery of fish farming technology owned by the partner group. In addition, to increase production targets required sufficient capital, especially for the purchase of fish feed, it takes seriousness in fish farming, especially related to water quality management, feed management, harvest handling and marketing. Therefore, it is imperative to transfer science and technology to solve those problems. Method of implementation of Science and Technology for Society (IbM) done in several stages of socialization and discussion, technical and non technical training, business management and marketing training. After the training activities have been completed, the process of mentoring and monitoring of the partner groups were conducted. The outcome of these activites was the product of fish feed made from local raw materials. Keywords: fish farmer; Tunas Muda Village; feed fish